Heroin use, HIV-risk, and criminal behavior in Baltimore: Findings from Clinical Research - Schwartz, Robert P. (J Addict Dis, 2015)
This paper reviews research conducted in Baltimore over the past 15 years that examined accessibility and barriers to methadone treatment, compared those who enter treatment to those who do not, studied retention and counseling issues, as well as the impact of treatment on criminality, HIV risk among participants and overdose death in the community. Recommendations to develop policies are presented to reduce heroin use and its negative impact in the community.